Nilai-Nilai Sufistik Dalam Puasa Kajian Tafsir Tarjuman Al- Mustafid Karya Abdul Rouf As Singkili - Ali Muammar Hasibuan; Hasan Bakti Nasution (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Fasting is one of the pillars of Islam that serves not only as a legal obligation but also as a means of purifying the soul and controlling human desires. In the Sufi tradition, fasting is regarded as a form of riyāḍah al-nafs (spiritual training) that cultivates spiritual awareness and draws believers closer to Allah. This study aims to examine the Sufi values embedded in fasting as interpreted by Abdul Rauf al-Singkili in Tarjuman al-Mustafid and to analyze their relevance for shaping contemporary Muslim spirituality. Employing a qualitative approach with a library research method, this study uses Tarjuman al-Mustafid as the primary source and classical Sufi texts as well as modern scholarly works as secondary sources. The findings reveal that Abdul Rauf emphasized four key values of fasting: sincerity, self-restraint, spiritual awareness, and the stages of takhalli, tahalli, and tajalli. These values contribute to the development of a pious Muslim character and offer solutions to modern challenges such as consumerism, hedonism, psychological stress, and moral decline. This research highlights that Tarjuman al-Mustafid not only enriches the heritage of Qur’anic exegesis in the Malay-Indonesian world but also remains highly relevant in strengthening spirituality and character education among Muslims in contemporary contexts.